To GT or Not to GT…What’s a Girl to Do? A Look into Feminist Grounded Theory - Geleana Drew Alston (Adult Education Research Conference, 2014)
What is grounded theory really all about? Can using the constant comparative method qualify a study as being a grounded theory study? What is the difference between classical grounded theory and constructivist grounded theory? Is it wrong to identify a theoretical framework prior to the initiation of the study? Is it wrong to review literature prior to collecting and analyzing data when using a grounded theory approach? Is it appropriate to use other coding techniques in addition to open coding, axial coding, and selective coding? These and many other questions may trouble the novice grounded theorist during the design stage of her or his research study. For sure, grounded theory involves a different level of complexity because it is a systematic, but flexible process of collecting and analyzing data with the aim of generating new theory (Birks & Mills, 2012; Charmaz. 2006; Glaser & Strauss, 1967; Patton, 2002). To add, a grounded theory approach is appropriate to use when exploring a phenomenon wherein little research has been done or little is know about the subjects or phenomenon (Birks & Mills, 2011). Therefore, it is imperative for the researcher to understand what grounded theory is, what grounded theory is not, and what grounded theory can be.